An Alternative Method of Endoscopic Intrasphenoidal Vidian Neurectomy. Issue 1 (March 2018) - Zhao, Changqing; Ji, Yongjin; An, Yunfang; Xue, Jinmei; Li, Qingfeng; Suo, Limin; Hou, Ran; Zhang, Yanting; Geng, Zhigang; Shen, Huimei; Ren, Jianjun; Yang, Pingchang
Objective: To develop an easy surgical approach to facilitate clinical management. Study Design: A novel transnasal endoscopic 3-step surgical method for vidian neurectomy was designed and tried in 91 cases with a mild-to-severe degree of allergic and nonallergic rhinitis refractory to routine medical therapy. Setting: Endoscopic vidian neurectomy requires accurate localization of the vidian canal. However, it is not easy to localize during surgery because of its deep location and the complex anatomy of the pterygopalatine fossa. Subjects and Methods: This technique consists of 3 steps, including transnasal endoscopic perforation of the anterior wall of the sphenoidal sinus as the first step and removal of the anterior wall until the exposure of the vidian canal in the junction between the anterior wall and the floor of the sphenoid sinus as the second step. The last step is the accurate resection and cauterization of the vidian nerve. In some cases in which the sphenoid sinus developed well with a big lateral space, an extended procedure of posterior ethmoidectomy was included to allow good exposure of the vidian canal. Results: Using this technique, successful endoscopic vidian neurectomy in this series of patients was confirmed by both histology and Schirmer test, showing its distinct advantages of easy localization of the vidian canal and less risk of injury to the nerve and vessel bundles within the pterygopalatine fossa. Conclusion: Taken together, this novel 3-step procedure of endoscopic vidian neurectomy plus an extended procedure guarantees good exposure of the vidian canal and therefore accurate vidian neurectomy.